Representasi Pergaulan Bebas dalam Film “Dua Garis Biru (2019)” dalam Perspektif Al-Qur’an - Afifah Syazwani Solihin; Muhammad Atthar Pramudita Rahmat; Sayyidah Nur Latifah; Siti Rohimah; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The phenomenon of promiscuity, which is now rampant, has many serious impacts on the lives of teenagers. This behavior is often normalized and portrayed in the media; one example of a media outlet that addresses this issue is the film Dua Garis Biru. This study aims to examine the representation of promiscuity and out-of-wedlock pregnancy in the film *Dua Garis Biru* through the perspective of the Qur’an, specifically in Surah Al-Isra’: 32, An-Nur: 30–31, Al-Mu’minun: 5–7, and An-Nisa’: 25. Using a thematic exegesis (tafsir maudhu'i) approach and anomie theory, this study analyzes how the film depicts the gradual process of moral deviation among adolescents, ranging from emotional intimacy to ultimately resulting in pregnancy outside of marriage. The method employed is descriptive qualitative research utilizing observation, documentation, and literature review techniques. The sample consists of selected scenes chosen through purposive sampling. The results indicate that the film’s depictions reflect forms of behavior approaching adultery, as prohibited in QS. Al-Isra’: 32. The interpretations of Ibn Kathir and Al-Qurtubi affirm that this prohibition is preventive in nature, meaning it closes all paths leading to moral transgression. The theory of anomie explains that the weakening of social control and norms in the lives of modern adolescents is a driving factor behind deviant behavior. This study demonstrates that Qur’anic values remain relevant in addressing contemporary social phenomena and highlights the importance of strengthening religion-based moral education.